Dampak Psychological Empowerment pada Kinerja Karyawan - Aas Astri Aisyah; Harmon Harmon (Jurnal Riset Bisnis dan Investasi, 2015)
This research was conducted on employees at The Office of Regional Operation 2 Bandung PT Kereta Api Indonesia (Persero) with the number of respondents as many as 113 people. This research uses quantitative approach and survey method with the primary data collection technique using a questionnaire. The results of the research indicate that psychological empowerment has a positive and significant effect on job performance. This relationship suggests that if psychological empowerment that employees have a good/high, it will be followed by an increase in job performance and vice versa. These findings are similar to some previous research that states, intrinsic motivation in the form of psychological empowerment have a positive and significant effect on job performance.